Short-term Effects of Biochar Application on Soil Loss During a Rainfall-Runoff Simulation. Issue 1 (February 2019) - Khademalrasoul, Ataallah; Kuhn, Nikolaus J.; Elsgaard, Lars; Hu, Yaxian; Iversen, Bo V.; Heckrath, Goswin
Abstract : ABSTRACT: Application of biochar to soil has been suggested as a nonstructural best management practice to mitigate runoff potential and soil loss. However, empirical data substantiating these effects are still scarce. Rainfall was presently simulated under controlled conditions to study the effects of biochar on erosion and runoff potential with sandy loam soil sampled from a field experiment 2 years after biochar amendment (2 kg m −2 ). The field experiment comprised four untreated and four biochar-treated plots that were amended with biochar produced from birchwood. In the laboratory, aggregate stability and organic carbon (OC) in topsoil (0–0.2 m) were analyzed. Soil loss and runoff were measured during a 3.5-h rainfall simulation using a round flume setup. Organic C was also determined in the eroded sediment, soil crust, and bulk soil of each flume after simulations. While runoff was not affected by treatment, biochar-treated soils showed significantly lower soil loss rates compared with untreated soils, reducing the cumulative soil loss by 41%. This was attributed to the aggregating effects of OC from the biochar application and delayed crust formation. The reduced erosion of OC from biochar-treated soils also resulted in lower OC enrichment ratios in the sediment and thus less OC export than from untreated soils. The results illustrated that biochar application already in the short term (2 years) can lead to an improvement of soil aggregation, thereby enhancing aggregate stability and leading to a reduction in soil loss. However, extrapolation of these positive results must be done with caution because the scale of the flume limited the erosive forces acting on the soil. Before an extrapolation of the results, an upscaling of erosion tests to field scale is therefore required.